4CPS-031 Therapeutic drug monitoring of ceftazidime/avibactam administered by continuous infusion: PK/PD target achievement and clinical outcomes. Issue 1 (23rd March 2023) - Fresan, D; Luque, S; Miedes, J; Bosch, C; Benítez-Cano, A; Sorlí, L; De-Antonio, M; Prim, N; Vega, V; Horcajada, JP; Grau, S
Abstract : Background and Importance: Ceftazidime/avibactam (CAZ/AVI) is a novel betalactam antibiotic utilised for multi-drug resistant (MDR) gram-negative bacteria. Therapeutic drug monitoring (TDM) ensures that CAZ/AVI levels achieve the pharmacokinetic/pharmacodynamic (PK/PD) target. Continuous infusion (CI) has been used to optimise CAZ/AVI pharmacodynamics. Aim and Objectives: To analyse the correlation between PK/PD target attainment of CAZ/AVI administered by CI, clinical outcomes and toxicity. Material and Methods: Patients treated with CAZ/AVI administered by CI and undergoing TDM of the CAZ plasma concentrations were included. Definitions: CAZ/AVI PK/PD target: time that CAZ free concentrations remain 4 times above the minimum inhibitory concentration (MIC) of the causative pathogen (% f T>4xMIC). Overexposure:% f T>10xMIC. Clinical cure: disappearance of all signs and symptoms related to the infection and no requirement for additional antibiotic treatment initiation (except as part of de-escalation strategy) for the disease to be investigated within 48h after completion of the study drug. Thirty-day all-cause mortality: death from any cause during the 30 days following the end of treatment. When real MIC was not available, a MIC of 8 mg/L was assumed. Results: Thirty-one patients (28 males, median (range) age of 64 (37-78) years) infected with extensively drug-resistant Pseudomonas aeruginosa and extended-spectrum betalactamase-producing Klebsiella pneumoniae were included (26 directed treatments and 5 empirical). Twenty-six (83.9%) achieved the PK/PD target, 15 of which presented overexposure. Only 4 (26.6%) overexposed patients presented adverse reactions (3 increased liver enzymes and 1 thrombocytopenia). Twenty-one (67.7%) patients achieved clinical cure, 18 (85.7%) of which achieved the PK/PD target. There was a higher frequency of patients with a% f T>4xMIC that achieved clinical cure (18/26 (69.2%) in patients with clinical cure vs 2/5 (40%) with clinical failure, p= 0.686). The 30-day all-cause mortality was 19.4% (6 patients). A lower mortality rate was observed in patients that did achieve a% f T>4xMIC (14.8%) in patients who survived vs 50% in those who died, p=0.096. Conclusion and Relevance: CI seems a useful strategy to reach the PK/PD target of CAZ/AVI. Few patients with overexposure presented adverse events. There seems to be a correlation between PK/PD target attainment, clinical cure and 30-day all-cause mortality but larger studies with bigger samples are needed. References and/or Acknowledgements: Conflict of Interest: No conflict of interest